2020
DOI: 10.3389/fbioe.2020.00852
|View full text |Cite
|
Sign up to set email alerts
|

Precision Engineering of the Transcription Factor Cre1 in Hypocrea jecorina (Trichoderma reesei) for Efficient Cellulase Production in the Presence of Glucose

Abstract: In Trichoderma reesei, carbon catabolite repression (CCR) significantly downregulates the transcription of cellulolytic enzymes, which is usually mediated by the zinc finger protein Cre1. It was found that there is a conserved region at the C-terminus of Cre1/CreA in several cellulase-producing fungi that contains up to three continuous S/T phosphorylation sites. Here, S387, S388, T389, and T390 at the C-terminus of Cre1 in T. reesei were mutated to valine for mimicking an unphosphorylated state, thereby gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…It has been reported that cellulase gene expression can be regulated by the dynamics of protein phosphorylation and dephosphorylation, which involve protein kinases and phosphatases, respectively ( Schmoll et al, 2016 ). Furthermore, in filamentous fungi, phosphorylation is a prerequisite for CRE1 activity ( Cziferszky et al, 2002 ; Han et al, 2020 ; de Assis et al, 2021 ). Therefore, in T. harzianum , it is important to elucidate the role of kinases and phosphatases in the regulation of CRE1 function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cellulase gene expression can be regulated by the dynamics of protein phosphorylation and dephosphorylation, which involve protein kinases and phosphatases, respectively ( Schmoll et al, 2016 ). Furthermore, in filamentous fungi, phosphorylation is a prerequisite for CRE1 activity ( Cziferszky et al, 2002 ; Han et al, 2020 ; de Assis et al, 2021 ). Therefore, in T. harzianum , it is important to elucidate the role of kinases and phosphatases in the regulation of CRE1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Upon glucose depletion, the concentration of CRE1 in the nucleus rapidly decreases, and CRE1 is recycled into the cytoplasm ( Lichius et al, 2014 ). Furthermore, the phosphorylation of CRE1 plays an essential role in signal transduction to achieve CCR ( Horta et al, 2019 ; Han et al, 2020 ). CRE1 is the only conserved TF throughout the fungal kingdom, suggesting a conserved mechanism for CCR in fungi ( Adnan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of carbon sources e.g., glucose and related sugars represses the transcription of certain genes. As a sequence-specific TF, CRE1/CreA plays a central role in CCR and is essential for the adaptation and survival of several species, such as Aspergillus , Penicillium , and Trichoderma [ 8 , 13 , 15 ]. In T. reesei , TrCRE1 rapidly shifts from cytoplasmic to nuclear with glucose addition [ 14 ] and represses the expression of glucose-repressible cellulolytic genes (such as cbh2 or egl1 ) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellulolytic gene induction requires a release from CCR. Therefore , the deletion, truncation, or multisite-directed mutagenesis of gene cre1 / creA can alleviate CCR and thus improve the expression level of prominent cellulolytic genes in various carbon sources, such as glucose, lactose, sophorose, cellulose, or a mixture of plant polymers [ 5 , 15 18 ]. For example, either the deletion or truncation of cre1 in T. reesei wild-type strain QM6a leads to de-repressed production of cellulase and hemicellulase, when the mutants are cultivated in glucose-containing media [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the substitutions of these phosphorylation sites with alanine had a significant effect on CreA degradation under de-repressing conditions ( de Assis et al, 2021 ). A recent study showed that replacement of S388 at the T. reesei Cre1 C-terminus with valine releases CCR ( Han et al, 2020 ). This serine residue is conserved in the Aspergillus CreA proteins.…”
Section: Carbon Catabolite Repression Of Hydrolytic Enzyme Genesmentioning
confidence: 99%